ТУРИЗМ ТАРАЎЫНЫҢ БҮГИНГИ КҮНДЕГИ ӘҲМИЙЕТИ - Турениязова, Д.Қ.; Аметов, А.К. (FAN va JAMIYAT, 2025)
The article examines the current development of the tourism industry, the term "tourism," the role of tourism in the global community, and its significance in social life.